IMPLEMENTATION OF SOCIAL EDUCATION IN NATIONAL CHARACTER BUILDING - Warlim; Mujahidin (International Journal of Teaching and Learning, 2025)
This research examines the implementation of social education in national character building, highlighting the importance of developing character with integrity and civilised through a holistic approach. Social education is not only limited to the academic environment but also covers various aspects of life, including family and community. Through curricula that emphasise civic education, extracurricular activities and community programmes, individual character can be firmly established. In addition, the active role of families and the media in instilling moral values also supports this process. The results show that the synergy between formal education, social participation, and environmental support is crucial in building a solid and sustainable national character amidst complex global dynamics.